"A national resource of primary importance:" Transforming Ireland's peatlands in the twentieth century - Toomey, Lily (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
This research is concerned with the industrialisation of peat extraction in Ireland in the twentieth century and the subsequent contributions of this national resource to changing modes of energy conversion and utilisation in the modernising Irish state. The Irish peat industry was established in the 1930s to contribute to the government's wider objectives of national and regional development. Peat was framed as a national resource and a means through which to establish energy independence. This industry grew throughout the twentieth century, eventually contributing to the large-scale transformation of communities and ecosystems at the sites of extraction, as well as establishing pathways for increased fossil energy consumption in Ireland. This research questions the beliefs and assumptions underpinning the state's decision to place peat at the centre of Irish state-building policies and considers the influences and experiences of non-governmental actors and more-than-human agencies in shaping the peat energy system. This thesis develops an environmental history of the peat energy regime, from its origins in imperial resource-making discourses, to its resistance by ecologists and conservationists in the 1980s. Within this timeframe, peatlands were entirely remade as sites of industrial extraction, the materiality of peat was transformed into electricity, and the domestic consumption of peat became increasingly detached from its extractive origins. In tracing the discourses and material realities surrounding the changing peat energy system in Ireland, this thesis bridges the gap between cultural resource imaginaries and the realities of human-nature entanglements at the sites of extraction and consumption. Rather than developing a narrative of decline, this thesis demonstrates that ecological decline was in fact part of a wider history of state-building, community and identity formation, and new living standards for Irish people. For this reason, the socio-cultural attachments to peat energy are shown to be deeply rooted. Furthermore, in considering the emergence of a peatland conservation paradigm, this research identifies that the interdependencies between industry, ecology, and agriculture situated emergent peatland management principles within entrenched economic objectives.
APPROVED
Keywords: peat; peatlands; environmental history; energy history; twentieth century Ireland; resource imaginaries; modernisation; history of ecology; labour and nature; colonial legacies